2021
DOI: 10.3390/ani11113217
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor Coregulators Can Modulate the Action of Progesterone Receptor during the Estrous Cycle in Cow Endometrium

Abstract: Nuclear receptor coregulators include coactivators and corepressors which associate with the progesterone receptor (PGR) during its activation. Fluctuations in the transcription levels of their respective genes and subsequent protein production as well as in related activities for histone acetyltransferase (HAT) and histone deacetylase (HDAC) can affect PGR function and thus change the action of progesterone (P4) in bovine endometrium during the estrous cycle. Endometrial tissue on days 2–5, 6–10, 11–16, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…We have previously shown that coactivators and corepressors demonstrate variable expression during the estrous cycle in the CL [10] and endometrium [11]. We have also presented that luteotropic factors (luteinizing hormone (LH), prostaglandin E2 (PGE2), and E2) and luteolytic factors (prostaglandin F2α (PGF2α) and nitric oxide) regulate PGRA and PGRB expression [12].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that coactivators and corepressors demonstrate variable expression during the estrous cycle in the CL [10] and endometrium [11]. We have also presented that luteotropic factors (luteinizing hormone (LH), prostaglandin E2 (PGE2), and E2) and luteolytic factors (prostaglandin F2α (PGF2α) and nitric oxide) regulate PGRA and PGRB expression [12].…”
Section: Introductionmentioning
confidence: 99%